2023
DOI: 10.2147/jaa.s389402
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Induced-Sputum Inflammatory Phenotypes in Adults with Asthma: Predictors of Bronchial Eosinophilia

Abstract: Purpose The objectives of this study were, for patients attending a specialist asthma clinic at a tertiary care hospital, to determine, from sputum induction (SI), proportions of bronchial inflammatory phenotypes, demographic, clinical and functional characteristics of each phenotype, and the most accessible non-invasive inflammatory marker that best discriminates between phenotypes. Patients and Methods Included were 96 patients with asthma, attending a specialist asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
0
1
Order By: Relevance
“…[49][50][51] Asthmatics treated with moderate ICS in FAO group had similar FeNO levels and sputum eosinophil percent to those of unselected asthmatics and those of well-controlled asthmatics, [52][53][54] whereas both biomarkers were lower than those of uncontrolled asthmatics. 55,56 We did not find the association between both biomarkers and FAO status and the relationship of eosinophil activation with FAO status as demonstrated by others. 57 However, our results confirmed earlier studies that aging was associated with FAO and lower FeNO concentrations as demonstrated by the evidence that asthmatics with FAO were significantly older and tended to have lower FeNO levels, albeit statistically insignificant, than asthmatics with nFAO.…”
contrasting
confidence: 48%
“…[49][50][51] Asthmatics treated with moderate ICS in FAO group had similar FeNO levels and sputum eosinophil percent to those of unselected asthmatics and those of well-controlled asthmatics, [52][53][54] whereas both biomarkers were lower than those of uncontrolled asthmatics. 55,56 We did not find the association between both biomarkers and FAO status and the relationship of eosinophil activation with FAO status as demonstrated by others. 57 However, our results confirmed earlier studies that aging was associated with FAO and lower FeNO concentrations as demonstrated by the evidence that asthmatics with FAO were significantly older and tended to have lower FeNO levels, albeit statistically insignificant, than asthmatics with nFAO.…”
contrasting
confidence: 48%
“…There was an almost equal distribution of EA (n = 25) and MGA (n = 24), while 19 subjects had PGA and 12 subjects had NA in the whole cohort. Other studies have also found EA to be the most prevalent phenotype, presented in 41%, 40%, and 46.9% of patients, respectively, but the distribution of the other three phenotypes was varying [9,30,31]. The predominance of the PGA phenotype was seen among 176 patients with asthma in China, in 42.6% [32].…”
Section: Discussionmentioning
confidence: 82%
“…We did not confirm the correlation between the number of eosinophils in blood and the % of eosinophils in sputum among patients with EA (ρ = −0.03, p = 0.863). The correlation between serum and sputum eosinophilia is seen in many studies [31,33,34]. Schleich et al have shown this connection in more than 500 asthmatics, and they have set the cut-off value of 220/µL of blood eosinophils to identify ≥3% eosinophils in sputum [35].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation